FKIK Bebas Sampah Plastik: Pengembangan Media Promosi Kesehatan pada Tatanan Khusus dalam Mewujudkan Kampus Sehat - Reskiaddin, La Ode; Rahmat, Andree Aulia; Siregar, Sri Astuti; Perdana, Silvia Mawarti; Prasetyo, Yodi (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2024)
The increasing use of plastic waste in Indonesia has an impact on many sectors. Jambi University's Faculty of Medicine and Health Sciences is committed to addressing waste issues through the Dean's policy. However, the application of the policy is still not optimal, especially regarding health promotion media related to plastic waste and other matters related to disposable packaging waste. This service aims to develop health promotion media to support the dean's policy. This service was carried out in the Faculty of Medicine and Health Sciences (FKIK), Jambi University. The method of community service activities includes (1) Coordinating with partners regarding the implementation of activities (2) Searching for literature for the development of educational content (3) Preparing educational messages and forms to be developed (5) Designing educational media in certain settings (6) Making educational posters (7) Distributing educational media. The output of community service is the creation of health promotion media on glasses, jars, plates and teapots that have been applied in campus activities, especially in the dean's meeting room. In addition, several posters that have been made are distributed in the FKIK campus of Jambi University. The need for more massive distribution within the university and developing other media to realize a healthy campus.